Estrategias metodológicas para mejorar la calidad de enseñanza en los laboratorios de informática de los estudiantes de séptimo semestre de la Carrera de Comunicación Social 2022 - Mendez Mendoza, Uber Elias (2022)
The present project touches the subject of university problems, where the methodological strategies is the point of attention, so this case study was developed following the objective of analyzing the use of methodological strategies to improve teaching in computer labs, where the direct beneficiaries are the students of the seventh semester of Social Communication, for which a descriptive methodology was followed in the research, with a numerical or quantitative approach to obtain figures that allow to deduce accurately once the results are observed, For which we worked with 26 students of the course through a digital survey, reaching the conclusion that an improvement is suggested in the way the methodological strategies are developed for the computer lab and show nonconformity in the survey, making a recommendation to improve teaching strategies relying on quality teaching materials and also improve the commitment that students should have with research projects that benefit the career and the university, through reflective or ethical talks to improve the criterion of responsibility.